The role of DRD4 DNA methylation in schizophrenia - Abd. Rahim, Nour El Huda; Rahim Mohd, Nabil Fikri; Ku Zaifah, Norsidah; Mohd Noor, Hanisah; Abdull Jalil, Mohd Asyraf; A.Talib, Norlelawati (2021)
Introduction: DRD4 is a dopamine receptor subtype that has been linked to schizophrenia genetically. Previous studies have shown that the density of DRD4 in schizophrenics' brains was higher than the other dopamine receptors. However, the genetic research of DRD4 in the physiology of the dopaminergic system with increased risk of schizophrenia is still not well established. Due to the complexity of the gene variations associated with schizophrenia and the influence of environmental factors, the study aimed to analyse the DRD4 DNA methylation in the peripheral blood of schizophrenia. Materials and Methods: This study was a casecontrol study. A total of 138 schizophrenia patients were recruited from the Psychiatry Clinic, Hospital Kuantan Ampuan Afzan, Kuantan Pahang and 132 matched healthy controls were included from Kuantan district. The genomic DNA from the peripheral blood was extracted and bisulfite converted. The MethyLight Taqman® test was used to determine the degree of DRD4 DNA methylation quantitatively. The data was analysed using analysis of covariance (ANCOVA) after being adjusted for age and gender. Results: When compared to the control group, schizophrenia had significantly lower DRD4 DNA methylation (p=0.001). Males (p=0.026) and females (p=0.004) patients both had hypomethylation. Conclusion: This research strongly suggests that DNA methylation of the DRD4 gene may have a role in the genetic foundation of schizophrenia.